Olmesartan medoxomil-induced acute renal failure in a premature newborn following maternal exposure during pregnancy: A case report and review of the literature - Dathan, Krishna; Lakhshmi, V (Indian Journal of Case Reports, 2018)
Angiotensin-converting enzyme inhibitors and angiotensin II receptor blockers (ARBs) are widely used antihypertensive with well-recognized renoprotective and cardioprotective effects. Although treatment with these agents generally does not result in adverse metabolic consequences, their use during human pregnancy has been associated with negative reactions. Here, we report a premature baby with a history of oligohydramnios and maternal exposure to the ARB olmesartan medoxomil who was transferred to our institution with acute renal failure.